Візантиністика у Харківському університеті (середина ХІХ – початок ХХ ст.) - Домановська, М.Є. (My University, 2015)
У дисертації вперше здійснено дослідження процесу становлення і розвитку візантиністики як наукової та навчальної дисципліни в Харківському університеті (середина ХІХ – початок ХХ ст.). Запропоновано його періодизацію, схарактеризовані політичні та соціокультурні умови зародження візантиністики у Харківському університеті. Визначено коло вчених-візантиністів, схарактеризовано їхній творчий спадок, акцентовано увагу на ролі візантинознавчої складової у навчальному процесі. Проаналізовано наукові комунікації зазначеного кола науковців, розглянуто питання про існування візантиністичної наукової школи у Харківському університеті. В диссертации впервые осуществлено исследование процесса становления и развития византинистики как научной и учебной дисциплины в Харьковском университете (середина ХІХ – начало ХХ вв.). Предложена его периодизация, охарактеризованы политические и социокультурные условия зарождения византинистики в Харьковском университете. Определен круг ученых-византинистов, дана характеристика их научного наследия, акцентировано внимание на роли византиноведческой составляющей в учебном процессе. Проанализированы научные коммуникации упомянутого круга ученых, рассмотрен вопрос о существовании византинистической научной школы в Харьковском университете. For the first time in Ukrainian historiography, this dissertation offers a systematic study of the emergence and development of Byzantine studies as a discipline and part of the curriculum at Kharkiv University (mid-nineteenth to early twentieth century). Author creates a periodization and explores the political and socio-cultural conditions for the development of Byzantine studies at the University. The dissertation defines the circle of Kharkiv scholars engaged in Byzantine studies and analyzes their work and its significance in the context of the general development of academic scholarship in this period and the condition of Byzantinology in particular. The role and place of Byzantine subjects in the general courses for the students of history and law is characterized, and the special courses in Byzantine studies taught at the University are described. Author analyzes the papers on Byzantine studies presented at the 12th Archeological Congress in Kharkiv and the scholarly activities and communications of the Kharkiv University faculty engaged in Byzantine studies. The question of the existence of a Byzantinological school at Kharkiv University is also considered. The dissertation argues that the development of Byzantine studies at Kharkiv University was influenced both by the general European trends in the humanities and by the peculiarities of the historical discourse in Russia, with its special stress on the significance of the Byzantine heritage in the culture and the traditions of state-building among the Eastern Slavs. Along with new and diverse research in Byzantine studies at Kharkiv University, the elements of disciplinary infrastructure were emerging: the number and range of courses was growing, the creation of a chair in Byzantine studies was considered, scholars from the University were taking part in setting up specialized journals in Byzantine studies and presented their work at specialized conferences and meetings. The main subjects of interest for the Kharkiv scholars engaged in Byzantine studies were: the political history of Byzantium (O. P. Zernin, M. N. Petrov, V. K. Nadler, E. O. Chernousov), Rus’-Byzantine connections (M. O. Lavrovsky, V. I. Savva), Byzantium and the Southern Slavs (P. O. Lavrovsky, M. S. Drinov, G. A. Ilyinsky), the history of the Byzantine Church (A. S. Lebedev), Byzantine and Rus’ art (O. I. Kirpichnikov, E. K. Redin, F. I. Schmidt).
https://byzantina.wordpress.com/2015/01/29/domanovska-9/
Keywords: Харківський університет; історична наука; візантиністика; славістика; мистецтвознавство; Харьковский университет; историческая наука; византинистика; славистика; искусствоведение; Kharkiv University; historiography; Byzantine studies; Slavic studies; art history